Methods to Describe and Measure Lighting Conditions in Experiments on Non-Image-Forming Aspects. Issue 2 (3rd July 2019) - Knoop, Martine; Broszio, Kai; Diakite, Aicha; Liedtke, Carolin; Niedling, Mathias; Rothert, Inga; Rudawski, Frederic; Weber, Nils
ABSTRACT: Research indicates that spectral distribution and the direction of the light received at the eye are relevant parameters in studies looking into non-image-forming effects. Nonetheless, lighting conditions are often described with vertical illuminance at the eye and correlated color temperature only, both of which are integral measurements that are not appropriate to give information about the spatial distribution of light and its spectrum. This article describes approaches for spatially and spectrally resolved measurements to properly quantify lighting conditions in research on non-image-forming effects. The overview of measuring methods indicates that the spectral irradiance, when combined with a luminance image of the lighting setting, is an adequate measure in a large number of research approaches. Nonetheless, lighting conditions in experimental setups with different light sources or various surface reflectances require a higher resolution of detail. Four examples of devices are presented that can be applied in different experimental setups or lighting settings. A decision scheme is included to support the selection of the most suitable measuring equipment. The article concludes with a proposal for analysis and representation of the measurements.